Optimizing maternal healthcare: Holistic strategies for early detection and management of preeclampsia - Asmanidar, Asmanidar; Emilda, Emilda (Science Midwifery, 2024)
Preeclampsia remains a serious challenge in maternal healthcare, with significant risks of complications for both the mother and the fetus. In this context, this research aims to explore holistic strategies for early detection and management of preeclampsia to optimize maternal healthcare. Through a comprehensive literature review, this article presents various approaches that have been implemented, including blood pressure monitoring, biomarker identification, and the use of prediction models for preeclampsia. The research findings highlight the need for an integrated approach between primary healthcare services and hospitals, as well as increased awareness and training for healthcare professionals in recognizing the symptoms and risk factors of preeclampsia. Furthermore, the article emphasizes the importance of interdisciplinary collaboration and further research to develop more effective and efficient strategies in managing this condition. Therefore, the optimization of maternal healthcare requires a holistic approach that encompasses early detection and management of preeclampsia to improve overall maternal and neonatal health outcomes.